The Academic Motivation and Engagement of Students in English as a Foreign Language Classes: Does Teacher Praise Matter? - Peng, Chunju (Frontiers in Psychology, 2021)
Given the undeniable role of English as a foreign language (EFL) students’ academic motivation and engagement in L2 success, identifying the antecedents of these positive academic behaviors seems essential. Accordingly, many empirical studies have probed into the impact of students’ personal factors on their motivation and engagement. Yet, not much attention has been paid to the role of teachers’ communication behaviors, notably praise. Additionally, no review has been performed in this regard. The present review study intends to address these gaps by explaining teacher praise and its positive outcomes for EFL students’ motivation and engagement. In light of the empirical and theoretical evidence, the role of teacher praise in improving students’ academic motivation and engagement was proved. The paper concludes with some pedagogical implications.